Water resources and their role in food security in Algeria: Analytical Study - Amrouci, Hanene; Rehimi, Aissa (International journal of economic perspectives, 2024)
This study aimed to identify the status of water resources in Algeria and their uses, as well as to diagnose the reality of food security in light of global food security indicators during (2019-2022), employing the descriptive and analytical approaches. The study concluded that: agricultural reforms contributed to improving agricultural productivity (cereals, oil, sugar, milk); however, Algeria has not yet achieved self-sufficiency in terms of the widely consumed substances. Besides, the effects of climate change on agriculture require Algeria to continuously develop appropriate